Pengaruh Orientasi Kewirausahaan dan Berbagi Pengetahuan Terhadap Inovasi Produk Serta Dampaknya terhadap Kinerja Produk Baru (Studi pada UMKM Batik di Kecamatan Lasem ) - Muhammad Ainul Huda; Endang Tjahjaningsih (Jurnal Mirai Management, 2022)
Abstrak The marketing strategy for Lasem batik is through social media and offline. Free promotions are carried out through Facebook, Twitter and Instagram to be put to good use and able to promote word of mouth to promote more widely. MSMEs also need to conduct market surveys to obtain information about Rembang batik design. This study aims to: (1) to test and analyze the effect of entrepreneurial orientation on product innovation, (2) to test and analyze the effect of knowledge sharing on product innovation, (3) to test and analyze the effect of product innovation on new product performance. The results of the first hypothesis test show that entrepreneurial orientation has an insignificant positive effect on product innovation. The results of the second hypothesis test show that knowledge sharing has a significant positive effect on product innovation. The results of the third hypothesis test show that product innovation has an insignificant negative effect on new product performance. The sampling technique in this study used accidental sampling, respondents were taken from this study were Batik UMKM as many as 100 respondents, the data analysis method used was multiple linear regression analysis. Kata Kunci: Orientasi Kewirausahaan, Berbagi Pengetahuan, Inovasi Produk, Kinerja Produk Baru